Analisis dan Perancangan Sistem Informasi Pengajuan Cuti Pegawai Menggunakan Pendekatan Object Oriented Analysis and Design (OOAD) (Studi Pada PT. Pos Indonesia Surabaya Kebonrojo) - Fiera Arnandya Rani; Satrio Agung Wicaksono; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT. POS Indonesia Surabaya Kebonrojo harnesses a plethora of management information systems. According to focus group interviews, there is an untapped need for managing employee leave applications through computerised information systems. Therefore, the focus of this paper aims to solve problems by focusing on analyzing and designing system designs. To answer this question, the Object Oriented Analysis and Design (OOAD) method was undertaken to analyse and design systems which consists of 5 stages: use case modelling, architecture analyzing, use cases analyzing, data elements identifying, and data modeling. This process involved synthesising archived interviews and documented studies to obtain an overview of business processes, analyse user needs, design use cases, state machine diagrams, activity diagrams, sequence diagrams, class diagrams, physical data models, and to interface designs. The testing segment was carried out using the Configuration Structure and Traceability Matrix methods. Results using Configuration Structure method revealed that there was high consistency in defining user requirements (100,00%). The testing segment of study using Traceability Matrix method ceased processes when functional requirements of use cases were consistent with the value of 100,00%.